Beyond instrumentalization: assessment of learning in Professional and Technological Education (Research, Society and Development, 2021)
The objective of this article is to discuss the assessment of learning in Professional and Technological Education. Considering that its purpose, for many, is restricted to the demands of the job market, the question is: should this type of education aim at the job market, the demands of business, or provide the student with an education that goes beyond this objective? For this purpose, the theoretical bases of instrumentation in education, arising from traditional and technical approaches, are presented, and the differences between the culture of instrumentalization and emancipation in relation to the assessment of learning are explained, positioning itself in favor of this last one mentioned as the most suitable for a liberating teaching practice. The methodology is based on a qualitative approach, with bibliographical and exploratory research. The current Law of Guidelines and Bases for National Education, the Common National Curriculum Base, and the National Curriculum Guidelines for Professional and Technological Education were also considered. Based on these studies, it can be concluded that the Professional and Technological Education must prepare students for beyond the job market demands.